Teaching Moral Values Through Real-life Dilemmas - Vishalache Balakrishnan (Nurul Jadid University, 2023)
The purpose of this study is to contribute to contemporary debates about alternative ways of teaching Moral Education (ME) in Malaysia by including the voice of students. ME in the Malaysian setting is both complex and compulsory. The research is founded on a modified version of Vygotsky’s Zone of Proximal Development (ZPD), extended to suit the multicultural, multi-ethnic Malaysian setting, and here called the Zone of Collaborative Development (ZCD). This study uses qualitative research methodology consisting of a modified framework of participatory action research (PAR) as the methodological framework. Data was gathered for textual analysis through a modified form of participant observation, focus group transcripts, interviews, and student journals. Findings show that students were concerned about moral issues and values not covered in the current ME curriculum. The moral dilemmas that they identified were relational and context dependent. Multiple factors contributed to the problems they described.